2013
DOI: 10.1159/000348368
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin and Its Relation with N-Terminal Brain Natriuretic Peptide, Endothelin-1 and Nitric Oxide in Patients with Idiopathic Pulmonary Hypertension

Abstract: Objectives: To investigate ghrelin levels in patients with idiopathic pulmonary arterial hypertension (IPAH) and the association of ghrelin with N-terminal brain natriuretic peptide (N-BNP), endothelin-1 (ET-1) and nitric oxide (NO). Methods: Plasma ghrelin, N-BNP, ET-1 and NO were measured, and echocardiography was performed in 20 IPAH patients and in 20 control subjects matched for age, sex and body mass index. Results: Plasma ghrelin and NT-proBNP levels were significantly higher in IPAH patients compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
(37 reference statements)
1
16
2
Order By: Relevance
“…In present study, pre-treatment with ghrelin did not have a notable influence on the iNOS protein expression in A549 cells induced by LPS, although it alone appeared to decrease the iNOS protein expression. Interestingly, our data showed that ghrelin could inhibit the NO production in A549 cells induced by LPS treatment, which was in contrast to what Yang et al reported that the NO production is in accordance with the increased plasma ghrelin levels in patients with idiopathic pulmonary arterial hypertension (IPAH) [35]. This contradiction may be attributable to that a small amount of NO could enhance vasodilation and regulate blood pressure [36,37], but excessive NO production, therefore, exert a harmful role.…”
Section: Discussioncontrasting
confidence: 99%
“…In present study, pre-treatment with ghrelin did not have a notable influence on the iNOS protein expression in A549 cells induced by LPS, although it alone appeared to decrease the iNOS protein expression. Interestingly, our data showed that ghrelin could inhibit the NO production in A549 cells induced by LPS treatment, which was in contrast to what Yang et al reported that the NO production is in accordance with the increased plasma ghrelin levels in patients with idiopathic pulmonary arterial hypertension (IPAH) [35]. This contradiction may be attributable to that a small amount of NO could enhance vasodilation and regulate blood pressure [36,37], but excessive NO production, therefore, exert a harmful role.…”
Section: Discussioncontrasting
confidence: 99%
“…Plasma BNP levels are elevated in adults and children with heart disease and PAH (idiopathic or congenital), so these levels serve as a useful laboratory parameter in medical or surgical treatment [23,24]. In our study we showed that all of the PAH patients had elevated levels of plasma BNP.…”
Section: Discussionsupporting
confidence: 51%
“…Ghrelin levels are three-fold higher in women than in men (90). Increased levels of circulating ghrelin are observed in IPAH (91). However, paradoxically, in MCT or hypoxic rat models the administration of ghrelin reduces PH (92,93).…”
Section: Synthesis Of the Literature On Sex Bias Mediated By The Neurmentioning
confidence: 98%
“…Thus, ghrelin is protective in rodent models but elevated in IPAH. In this instance, ghrelin has a central effect (stimulates GHRH and thus GH secretion, as in humans) and a different peripheral effect (antagonizes endothelin-1) (91).…”
Section: Synthesis Of the Literature On Sex Bias Mediated By The Neurmentioning
confidence: 99%